2022
DOI: 10.29036/jots.v13i24.278
|View full text |Cite
|
Sign up to set email alerts
|

Customer Brand Personality, Dining Experience, and Satisfaction at Luxury Hotel Restaurants

Abstract: The study’s primary purpose is to investigate customer brand personality’s effect on their dining experience and satisfaction at luxury hotel restaurants in Malaysia. Also, this study tests the mediation effect of dining experience on the brand personality and satisfaction interrelationship. A structured survey gathered empirical data from 482 luxury hotel restaurant customers. The AMOS software evaluated the research model using structural equation modelling (SEM). This study verifies that customer brand pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…En el sector de la telefonía móvil, las expectativas, necesidades y deseos de los clientes están evolucionando, y la tecnología sofisticada innovará e inventará continuamente (Ahmad et al, 2022).…”
Section: Titleunclassified
See 2 more Smart Citations
“…En el sector de la telefonía móvil, las expectativas, necesidades y deseos de los clientes están evolucionando, y la tecnología sofisticada innovará e inventará continuamente (Ahmad et al, 2022).…”
Section: Titleunclassified
“…La industria de las telecomunicaciones móviles en Ecuador se ha convertido en uno de los sectores más rápidos con la aparición de varios rivales, que en los últimos dos o tres años ha aumentado drásticamente el número de suscriptores móviles (Ahmad et al, 2022). La reducción significativa en el costo de los teléfonos móviles y la mejora de los ingresos disponibles también hicieron que los clientes eligieran su telefonía móvil a un precio cada vez más económico.…”
Section: Titleunclassified
See 1 more Smart Citation
“…Research has shown career success from various perspectives, some papers offering guidelines for bringing it closer to career theory (Arthur et al, 2005). Career success knows periods in one's life when objective, extrinsic factors may have a greater impact (e.g., remuneration or promotion), while other times the subjective, intrinsic criteria are more important (e.g., job satisfaction) (Ismail et al, 2022;Shockley et al, 2016;Gattiker and Larwood, 1988;Judge and Bretz, 1994;Kotter, 1982). Nevertheless, the objective and subjective career success are positively related (Bray and Howard, 1980;Harrell, 1969;Judge and Bretz, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies are aware of the need for streamlining the risk management process, which comprises several dimensions. Besides market and business risks, companies focus on protecting their reputation and trademark (Ismail et al, 2022), reliability of their business partners and financial institutions. While in recent years, European companies saw the most serious threat to their business in the risk of loss of liquidity, exchange rate and reputational risk, nowadays, they focus on examining risks also related to the social responsibility of companies, economic, innovative and environmental performance, export-related risks (Ključnikov et al, 2022a) as well as risks related to the sustainability of business in a given sector (Přívara, 2021(Přívara, , 2022Přívara & Rievajová, 2021).…”
Section: Introductionmentioning
confidence: 99%